THE INFLUENCE OF ARTIFICIAL INTELLIGENCE CAPABILITIES ON EMPLOYEES’ PRODUCTIVITY AMONG INFORMATION TECHNOLOGY STAFF IN JAKARTA - Sylvia Diana Purba; Pedro Lybernando Cornellius (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2025)
This study aims to analyze the influence of AI tangible resources, AI intangible resources, and AI human skills on employee productivity. The research was conducted on 52 employees’ productivity in the information technology (IT) sector who have already implemented  AI in their daily tasks. The data were collected through social media platforms such as WhatsApp, X (formerly Twitter), and Instragram. The data were analyzed using SPSS version 29. The results indicate that AI tangible resources have a significant positive effect on employees’ productivity in the IT sector. Likewise, AI intangible resources also have significant positive effects. However, AI human skills have a significant negative effect on employees’ productivity. Overall, AI tangible resources, AI intangible resources, and AI human skills have a significant simultaneous effect on employees’ productivity